Census-based mortality study of fertiliser manufactures. Issue 4 (November 1982) - Fraser, P; Chilvers, C; Goldblatt, P
Abstract : This study was designed to investigate whether exposure to nitrate-containing dust during fertiliser manufacture was associated with an excess of deaths from cancer in general or specifically from cancers of the digestive tract, liver, lung, and bladder. It was based on data extracted from census schedules by the Office of Population Censuses and Surveys, occupational characteristics recorded by fertiliser workers at the 1961 and 1971 censuses of England and Wales being related to subsequent mortality ascertained through the National Health Service Central Register. The 1961 cohort, followed up until 1978, showed a "healthy worker effect" and no evidence of excess mortality from cancer at any site. The 1971 cohort also showed below average mortality during 1971-7 for all causes of death and for circulatory diseases, but there were more deaths from cancer than expected, due mainly to an excess of cancers of the lung and digestive tract. The excess of cancer was more pronounced, but not statistically significant, when compared with other employed men. Though the numbers for comparison were small, there was weak evidence of an association between cancer mortality and frequency of exposure to nitrate-containing dust in this cohort. It is difficult to reconcile the excess cancer mortality in the 1971 cohort with the more favorable level in the earlier cohort, since industrial hygiene has improved and the cohorts showed a similar distribution by region and social class. To examine further these conflicting results the 1971 cohort will be followed for a longer period and re-examined when more deaths have accrued.